Structure of the western Brooks Range fold and thrust belt, Arctic Alaska - De Vera, J.; McClay, K. (TRABAJOS DE GEOLOGÍA, 2009)
This study summarizes the structure of the western Brooks Range fold and thrust belt of Arctic Alaska. The fold and thrust exposes a series of NE-SW-trending, NW-transported and regionally folded thrust sheets. Emplacement of thrust sheets results from ophiolite obduction and telescoping of the ancient continental passive margin of Arctic Alaska in the Cretaceous. Integration of stratigraphic, structural and geophysical data suggests that the structure of the fold and thrust belt is controlled by inheritance of NW-SE-trending Paleozoic structures of the pre-existing continental margin.